Parametric Study of the Reinforcement Geometry on Tensile Loaded Scarf Adhesive Repairs - Moreira, R.D.F. (2016)
The recent enhancements in structural adhesives technology enabled the use of adhesive joints and repairs in several industrial fields. The scarf repair is the most efficient because of suppression of peel (σ) and shear (τ) peak stresses, arising from the tapered adherend edges. The repair of structures that have the requirement of flush surfaces is one of the major applications of the scarf geometry. This work is a numerical study on the ultimate tensile strength of two-dimensional (2D) scarf repairs of aluminum structures with external doublers as reinforcements. Two adhesives were considered: the brittle epoxy Araldite® AV138 and the ductile epoxy Araldite® 2015 (Huntsmann, Basel, Switzerland). The numerical analysis by finite elements (FE) was performed in Abaqus® (Dassault Systèmes, Vélizy-Villacoublay, France) and used cohesive zone models (CZM), thus enabling the strength prediction of the repairs. Validation of this methodology with scarf repair experiments was performed previously. The influence of the main reinforcement geometric parameters is studied for the two adhesives, such as doubler thickness and edge geometry. This work enabled to conclude that the repairs’ strength can be optimized by a significant amount by a careful selection of the doubler geometry, and that the results are dependent on the adhesive ductility.